Constrained ECG compression algorithm using the block-based discrete cosine transform - Benzid, R.; Messaoudi, A.; Boussaad, A. (Digital signal processing, 2008)
Presented is a novel method dedicated to ECG compression. It uses the block-based discrete cosine transform (DCT) and considers the percent root-mean-square difference (PRD) as a controlled quality criterion. The simple and efficient resulting lookup table coding in coordination with the non-zero resulting DCT coefficients adaptive linear quantization, proffer to the method a high performance. The experiments carried out on the MIT-BIH arrhythmia records point out its effectiveness and classify it as a valid concurrent to some recently published powerful methods.